Motivations and Attitudes Toward Further Education: A Cross-Sectional, Descriptive Predictive Study. - Sušilović, Ivana; Ljubičić, Marija; Matijaš, Tatjana; Bokan, Ivana; Marendić, Mario (Nursing Reports, 2025)
Background: Educational requirements in healthcare are constantly evolving, and understanding nurses' motivations toward continuing education is critical to designing nursing programs, developing workforce strategies, and ensuring better healthcare outcomes. Objectives: This study aimed to examine the relationships among nurses' personal factors, motivations, and attitudes toward further education. Methods: We conducted a cross-sectional study involving 526 employed nurses. Based on their intention to enroll in studies, the nurses were divided into two groups: those who intended to enroll (n = 276) and those who did not intend to enroll (n = 250). We used the Work Preferences Inventory and the Attitudes and Educational Intentions Scale to assess motivations and attitudes toward further education. The multivariate analysis included linear and logistic regression to assess associations between variables. Results: Nurses who intended to enroll in nursing studies had higher intrinsic motivation than nurses who did not. Strong negative associations were found between job challenges and older age (β = −0.68), while length of service was positively correlated (β = 0.46). A lower level of education had a negative effect on overall work motivation (β = −0.15) and attitudes toward future education (β = −0.09). Nurses with higher intrinsic challenge motivation (OR = 1.07) and a positive attitude toward further education (OR = 1.17) were more likely to study nursing. Conclusions: Intrinsic motivation, experience, and a positive attitude toward career advancement influence nurses' intentions to continue their education. To further motivate nurses, it is crucial to improve working conditions, offer advancement opportunities, and foster a culture that values their contributions and growth.